2011
DOI: 10.1371/journal.pone.0020489
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic Spindle Proteomics in Chinese Hamster Ovary Cells

Abstract: Mitosis is a fundamental process in the development of all organisms. The mitotic spindle guides the cell through mitosis as it mediates the segregation of chromosomes, the orientation of the cleavage furrow, and the progression of cell division. Birth defects and tissue-specific cancers often result from abnormalities in mitotic events. Here, we report a proteomic study of the mitotic spindle from Chinese Hamster Ovary (CHO) cells. Four different isolations of metaphase spindles were subjected to Multi-dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
42
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 80 publications
(161 reference statements)
5
42
0
Order By: Relevance
“…Previous works demonstrate that PGRMC1 specifically localizes to the mitotic spindle apparatus of different cell lines, 11,16,17 where it directly interacts with b tubulin and controls spindle microtubule stability. 11 The present study demonstrates that PGRMC1 directly interacts also with AURKB and that the extent of this interaction is highest during the final phase of granulosa cell division.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous works demonstrate that PGRMC1 specifically localizes to the mitotic spindle apparatus of different cell lines, 11,16,17 where it directly interacts with b tubulin and controls spindle microtubule stability. 11 The present study demonstrates that PGRMC1 directly interacts also with AURKB and that the extent of this interaction is highest during the final phase of granulosa cell division.…”
Section: Discussionmentioning
confidence: 99%
“…13,15 However, PGRMC1 is also found in other sub-cellular compartments where it probably exerts additional functions. In particular PGRMC1 associates to the mitotic spindle, 11,16,17 where it directly interacts with b tubulin 11 suggesting a role in the regulation of mitosis. Immunofluorescence studies have shown that PGRMC1 changes its localization dynamically during mitosis: it associates with the spindle apparatus in metaphase, while it localizes to the midzone and the midbody in anaphase and telophase/cytokinesis.…”
Section: Introductionmentioning
confidence: 99%
“…3 Interestingly, one protein that localizes to the mid-zone/mid-body is progesterone receptor membrane component-1 (PGRMC1). 4 This protein was initially identified in liver as a progesterone binding protein, which accounts for its name (For review see Cahill 5 ). However, PGRMC1 is expressed in many cell types and has progesterone dependent and independent actions depending in part on its cellular location.…”
mentioning
confidence: 99%
“…Recent studies in Xenopus revealed enriched localization to spindle microtubules of mRNAs encoding spindle proteins (Blower et al 2007). The spindle is a complex structure; proteomic studies of isolated spindles have identified .1100 spindle-associated proteins, of which nearly 400 are specific to spindles and shared with proteomic studies that incorporated DNAse digests to deplete DNA-associated proteins (Sauer et al 2005;Bonner et al 2011), indicating that a large array of proteins is needed to support spindle formation, maintenance, and function. Localized maternal mRNAs could be translated in situ to provide a local high concentration of proteins, while minimizing potential deficiencies related to limitations in the speed or extent of protein accumulation from elsewhere within the ooplasm.…”
mentioning
confidence: 99%